Correlación entre urticaria crónica y coagulación - Roizen G., Gigia (Revista Hospital Clínico Universidad de Chile, 2015)
Chronic urticaria (UC), defined as recurrence of wheals with or without angioedema for more than 6 weeks, is a quite common disease that may severely worsen the quality of life. Although the actual pathophysiological mechanisms are still unknown, what we do know is that the main cells involved in their pathology are mast cells and eosinophils. The present article reviews recent findings showing an additional pathogenic mechanisms in UC patients: activation of the coagulation cascade resulting in thrombin production. Several investigators have demonstrated the activation of coagulation that is due to the involvement of eosinophils and a tissue factor pathway with generation of thrombin potentially contributing to an increased vascular permeability. CU patients often present with elevation of coagulation and fibrinolysis markers, such as prothrombin fragment F1+2 and D-dimer, which correlate with the disease severity. Preliminary data indicate that anticoagulant treatment with heparin and warfarin may be effective in reducing the symptoms of this disorder.